1985
DOI: 10.1161/01.res.57.4.538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of development on coronary vasodilator reserve in the isolated guinea pig heart.

Abstract: SUMMARY. Morphological studies have demonstrated an age-related decrease in capillary density and capillary surface area in the developing heart. However, the consequences of these changes on myocardial perfusion are not known. We tested the hypothesis that the decreased capillary density is associated with a reduction in coronary blood flow reserve. To test this hypothesis, we studied coronary responses to adenosine and sodium nitroprusside administration, reactive hyperemia, and autoregulatory capacity. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
2

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 30 publications
5
11
2
Order By: Relevance
“…The present findings concerning the effect of maturation of rabbits on maximal coronary flow rates are similar to previous findings of Toma et al (17) in guinea pigs. These investigators found that postnatal growth and maturation were associated with a decrease in maximal coronary flow rate per unit cardiac mass during pharmacologic vasodilation of isolated hearts with adenosine and nitroprusside.…”
Section: Maximal Coronaryjlow Rates Several Factors May Have Con-supporting
confidence: 93%
See 1 more Smart Citation
“…The present findings concerning the effect of maturation of rabbits on maximal coronary flow rates are similar to previous findings of Toma et al (17) in guinea pigs. These investigators found that postnatal growth and maturation were associated with a decrease in maximal coronary flow rate per unit cardiac mass during pharmacologic vasodilation of isolated hearts with adenosine and nitroprusside.…”
Section: Maximal Coronaryjlow Rates Several Factors May Have Con-supporting
confidence: 93%
“…The differences in maximal flow rates in this study parallel changes in myocardial capillarity that have previously been demonstrated in immature and mature animals (17) and in response to long-term exposure of maturing rodents to hypoxia (1-3). Thus, it would seem most likely that they occurred as a consequence of differences in myocardial microvascular density and relative cross-sectional area of the myocardial microvascular bed (i.e.…”
Section: Maximal Coronaryjlow Rates Several Factors May Have Con-supporting
confidence: 85%
“…Although this area of research has received comparatively little attention, one study has concluded that coronary flow in isolated, 1-week-old guinea-pig hearts is as, or more, sensitive to exogenous adenosine as adult hearts (18). This appears consistent with a report that supported the importance of adenosine in the regulation of coronary flow in the newborn lamb (10).…”
Section: Introductionsupporting
confidence: 65%
“…- 32 Gain values of coronary autoregulation in sham-operated control rats in our study were slightly smaller than the values in in situ working hearts 1 - 33 or isolated, blood-perfused, empty beating hearts 1 of larger animals such as dogs. At present, however, no data concerning the pressureflow relation in blood-perfused hearts of small animals are available to compare with our data.…”
contrasting
confidence: 58%